Zn/F-doped tin oxide nanoparticles synthesized by laser pyrolysis: structural and optical properties - Dumitrache, Florian; Morjan, Iuliana P.; Dutu, Elena; Morjan, Ion; Fleaca, Claudiu Teodor; Scarisoreanu, Monica; Ilie, Alina; Dumitru, Marius; Mihailescu, Cristian; Smarandache, Adriana; Prodan, Gabriel (Beilstein Journal of Nanotechnology, 2019)
Zn/F co-doped SnO2 nanoparticles with a mean diameter of less than 15 nm and a narrow size distribution were synthesized by a one-step laser pyrolysis technique using a reactive mixture containing tetramethyltin (SnMe4) and diethylzinc (ZnEt2) vapors, diluted Ar, O2 and SF6. Their structural, morphological, optical and electrical properties are reported in this work. The X-ray diffraction (XRD) analysis shows that the nanoparticles possess a tetragonal SnO2 crystalline structure. The main diffraction patterns of stannous fluoride (SnF2) were also identified and a reduction in intensity with increasing Zn percentage was evidenced. For the elemental composition estimation, energy dispersion X-ray spectroscopy (EDX) and X-ray photoelectron spectroscopy (XPS) measurements were performed. In general, both analyses showed that the Zn percentage increases with increasing ZnEt2 flow, accompanied at the same time by a decrease in the amount of F in the nanopowders when the same SF6 flow was employed. The Raman spectra of the nanoparticles show the influence of both Zn and F content and crystallite size. The fluorine presence is due to the catalytic partial decomposition of the SF6 laser energy transfer agent. In direct correlation with the increase in the Zn doping level, the bandgap of co-doped nanoparticles shifts to lower energy (from 3.55 to 2.88 eV for the highest Zn dopant concentration).
Keywords: laser pyrolysis; nanoparticles; optical bandgap; Zn/F-doped SnO2